The problems of application of administrative responsibility for violation of restrictions on classes other paid work or business activity - Корчак, Наталія Миколаївна; Корчак, Ярослав Олександрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The article analyzes the judicial practice in cases related to violation of statutory restrictions on employment in other paid or business activity, and provided address certain main issues of this kind of administrative offense. Among the preventive anti-corruption mechanisms, directed to prevent corruption of the system in Ukraine, distinguishes restrictions on pluralism and the combination with other activities that establish for persons authorized to perform function of state or local government. Violation of restrictions on employment in other paid activity (except teaching, research and creative activities, medical and judicial practice, the practice of sports instructor) or business activities constitute an administrative offense and are the basis for the use of administrative penalty in the amount of 300 to 500 non-taxable minimum incomes of citizens with confiscation of the revenue from business or part of remuneration. Prepared article is the result of careful analysis of judicial practice, considering this category of cases. Found that in practice remains controversial issues of the term "combining". Separate decisions by judges about dismiss the case in violation of restrictions on combining individual in not the main place of job. It was found the fact of unequal application of the law on the establishment of the remuneration in combining job and the question about confiscation. Criticism of the authors is the practice of courts in deciding administrative cases involving violation of the restrictions on employment in other paid or entrepreneurial activity, limited by using of administrative penalty kick onlyin the basisformalities of crime. It is proposed that in a situation where it is not possible to establish the amount of the consideration received or business income or failure to obtainthem, but the proof of intention the person compensated for the provision of services or profit goal (getting undue advantage), adjudicationmust necessarily reflect the fact of "missing subject to confiscation".